Should we be "challenging" employees? A study of job complexity and job crafting. (April 2022) - Tian, Qing; Bai, Jingyi; Wu, Ting
Abstract: Given the prevalence of stressful job demands in the hospitality industry, understanding how employees appraise complex jobs in service situations becomes vital to enhance employee job crafting. Drawing upon the challenge-hindrance framework and the transactional theory of stress, we explore how the appraisal process as a health-impairment pathway may govern the relationship between job complexity and job crafting. We propose that energy depletion mediates the relationship between job complexity and job crafting, while psychological empowerment moderates the relationship between job complexity and energy depletion. During a three-wave survey, we collected 396 responses from hotel employees to assess the proposed moderated mediation effects. Results show that the relationship between job complexity and energy depletion is weaker for employees that have higher psychological empowerment than low. Psychological empowerment further mitigates the negative indirect effect of job complexity on job crafting through energy depletion. The indirect effect is weaker when psychological empowerment is higher. These findings have additional theoretical implications for hospitality management and provide suggestions that facilitate job crafting in the hospitality industry. Highlights: Examines the relationship between job complexity and job crafting based on the challenge-hindrance framework. Suggests energy depletion as a health-impairment mechanism in job complexity and job crafting relationship. Psychological empowerment strengthens the relationship between job complexity and job crafting through energy depletion. Psychological empowerment can turn perceived pain from undertaking complex jobs to gain.